Material Develoment of English for Specific Purposes (ESP) for Tourism Program at SMKN 6 Surabaya (RETAIN, 2016)
Material Develoment of English for Specific Purposes (ESP) for Tourism Program at SMKN 6 Surabaya Tery Kusumawardani English Education, Language and Art Faculty, State University Surabaya terykusumawardani@mhs.unesa.ac.id Esti Kurniasih, S.Pd, M.Pd English Education Department, Faculty of Language and Art, State University of Surabaya Estikurniasih87@yahoo.com Abstrak Berdasarkan Kurikulum 2013, materi pembelajaran untuk tingkat sekolah menengah atas disamakan. SMA dan SMK mendapat materi Bahasa Inggris yang sama sedangkan menurut teori English for Specific Purposes atau Bahasa Inggris bagi jurusan studi tertentu harus dibedakan. Menemukan buku panduan belajar Bahasa Inggris berdasarkan jurusan studi siswa juga tidak mudah. Ditambah lagi, para guru juga tidak punya banyak waktu untuk membuat materi Bahasa Inggris yang sesuai dengan jurusan studi siswa. Faktanya, pelajar SMK sangat memerlukan materi Bahasa Inggris yang sesuai dengan jurusan studinya agar memenuhi kebutuhan belajar. Jadi, sangat direkomendasikan untuk mendesain materi Bahasa Inggris yang sesuai agar memenuhi kebutuhan, minat, dan tuntutan pelajar, terutama pelajar SMK Program Pariwisata. Penelitian ini dilakukan untuk mengetahui apa saja isi materi pembelajaran yang harus ada dalam materi Bahasa Inggris dan untuk mengetahui respon guru terhadap pengembangan materi Bahasa Inggris di Program Pariwisata di SMKN 6 Surabaya. Penelitian ini menggunakan metode Deskriptif Kualitatif dan semua hasil penelitian akan dijelaskan dalam bentuk kata. Hasil dari penelitian ini menunjukan bahwa isi materi Bahasa Inggris yang harus ada di Program Pariwisata adalah aktivitas berbicara dan pengucapan dalam Bahasa Inggris; memperbanyak video dan gambar sebagai media; dan teknik tanya jawab. Jadi, materi Bahasa Inggris terdiri dari presentasi dan video di kelas sebagai perwujudan aktivitas berbicara, kosa kata dan pengucapan dalam Bahasa Inggris, materi pemahaman membaca, dan pengetahuan lainnya yang berhubungan dengan Program Pariwisata. Selain itu, respon guru terhadap materi sangat memuaskan dan lengkap dalam memenuhi kebutuhan, minat, dan tuntutan pelajar Program Pariwisata. Kata Kunci : pelajar sekolah menengah kejuruan, pengembangan materi, English for Specific Purposes(Bahasa Inggris untuk sekolah kejuruan), program pariwisata Abstract Based on the 2013 Curriculum, the English materials for senior high school level is equalized. Both senior high school and vocational high school learners get the same English materials while the English materials for senior and vocational high school learners should be distinguished based on English for Specific Purposes. It is quite difficult to find proper English textbooks in accordance to learners’ majors in vocational school. In addition, the teacher also does not have enough time to design the English materials for vocational school learners. In fact, vocational school learners strongly need to learn English in accordance to their major for several reasons. So, it is recommended to design the English materials which meet learners’ needs, interests, and demands, especially in Tourism Program. This study was aimed to explore the contents that should be included to design the English materials based on the needs analysis in Tourism Program at SMKN 6 Surabaya and to find out the teacher’s response toward the English material development in Tourism Program. The base of the study used Descriptive Qualitative and the results were explained in the form of words. The results showed that the contents that should be included in the English materials in Tourism Program at SMKN 6 Surabaya are speaking and pronunciation for language skill and component; videos and pictures for media; and asking and giving question for teaching technique. The English materials development consist of a lot of presentations for speaking practice, several videos to practice speaking, pronunciation, and vocabulary, reading passages and texts, and some knowledge that Tourism Program learners need to know. Furthermore, it was found out that the teacher had good comments for the English material development. The materials were too complete and had met the learners’ needs, interests, and demands. Keyword: vocational learners, material development, English for specific purposes (ESP), tourism program